EVALUATION OF THE ANTIBACTERIAL ACTIVITY OF CALCIUM ALGINATE BEADS MODIFIED WITH ETHANOLIC EXTRACT OF ADHATODA VASICA LEAF EXTRACT ON STAPHYLOCOCCUS AUREUS AND ESCHERICHIA COLI - Thomas, Deepa; M S, Latha; Thomas K, Kurien (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of the present study was to investigate the antibacterial activity of calcium alginate (Ca-ALG) loaded with ethanolic extract of Adhatoda vasica (A. vasica) leaves against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). Methods: Ca-ALG beads containing ethanolic extract of A. vasica leaves were developed by ionic gelation technique. The prepared Ca-ALG beads were characterized by Fourier-transform infrared (FT-IR) spectroscopy and scanning electron microscopy (SEM). The antibacterial effect of A. vasica leaf extract loaded Ca-ALG beads was examined against S. aureus and E. coli. Results: FT-IR studies revealed the cross-linking of ALG and calcium ions. The spherical morphology of the beads was designated by SEM. The prepared beads were found to display distinctive growth inhibition against S. aureus and E. coli. Conclusion: The antibacterial activity analysis indicated that the prepared beads have good activity against S. aureus and E. coli. The present study proposes a strategy to enhance antibacterial properties of ALG which are widely used in biomedical applications.